Introduction to "Orogenic Cycles: From Field Observations to Global Geodynamics". Issue 1 (25th January 2019) - Toy, Virginia; Manatschal, Gianreto; Rosenbaum, Gideon; Miller, Meghan; Carosi, Rodolfo
Abstract: This Special Section of Tectonics, entitled "Orogenic Cycles: From Field Observations to Global Geodynamics, " has been compiled in commemoration of our friend and colleague Dr. Marco Beltrando, who tragically passed away in a mountain accident on 8 December 2015. Key Points: This special section of Tectonics commemorates Associate Professor Marco Beltrando's early passing in December 2015 This introduction explains the significance of Marco's research It also introduces and summaries all papers in the volume and indicates how they are linked